Volume 3: Turbo Expo 2002, Parts a and B 2002
DOI: 10.1115/gt2002-30184
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of Stagnation Region Heat Transfer Due to Turbulence From an Advanced Dual-Annular Combustor

Abstract: Heat transfer measurements have been made in the stagnation region of a flat plate with an elliptical leading edge. The radius of curvature at the stagnation point was similar to that of a first stage turbine vane airfoil used in a large commercial high-bypass turbofan engine. The airfoil was mounted downstream of an arc segment of a dual-annular combustor similar to the type used in an advanced turbine engine. Testing was done in air at atmospheric temperature and at pressures up to 376 kPa to simulate the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
2
10
0
Order By: Relevance
“…The A summary of the measured turbulence intensities and length scales for three of the isothermal tests is shown in Table 3. The measured turbulence intensities were found to be in an elevated range from 20% < Tu < 30%, which is consistent with real combustor exit flows as reported by Cameron et al [7], Goebel et al [20], and Van Fossen and Bunker [13]. The main difference between these three tests was the position (porosity) of the center shutter at the inlet of the central chamber.…”
Section: Turbulence Intensity and Length Scalesupporting
confidence: 75%
See 1 more Smart Citation
“…The A summary of the measured turbulence intensities and length scales for three of the isothermal tests is shown in Table 3. The measured turbulence intensities were found to be in an elevated range from 20% < Tu < 30%, which is consistent with real combustor exit flows as reported by Cameron et al [7], Goebel et al [20], and Van Fossen and Bunker [13]. The main difference between these three tests was the position (porosity) of the center shutter at the inlet of the central chamber.…”
Section: Turbulence Intensity and Length Scalesupporting
confidence: 75%
“…It was also shown that the effect of temperature non-uniformities at the combustor exit was to reduce the overall cooling effectiveness on the vane by as much as 21%. Van Fossen and Bunker [13] studied heat transfer augmentation in the stagnation region of a flat plate with an elliptical leading edge. The test article was located downstream of an arc segment of a dual-annular combustor.…”
Section: Combustor-turbine Interactionsmentioning
confidence: 99%
“…The steady flowfield matches engine non-dimensional conditions (Mach number and Reynolds number) and the generated turbulence field, intensity and length scale, is consistent with recent reports from modern gas turbine engine combustors (Van Fossen and Bunker, 2002) and reports of turbulence decay through the first stage vane row Thole, 1998, 2000). The turbulence field simulates the core flow turbulence in the turbine, decoupling this turbulence from the turbulence in the wake.…”
Section: Introductionsupporting
confidence: 70%
“…Van Fossen and Bunker (2002) used a 60° section of a GE 90 dual-annular combustor in a wind tunnel to model the exit flow of a combustor, including inlet swirl vanes, film cooling holes and dilution holes. All three of these combustor components contribute strongly to the combustor exit turbulence conditions.…”
Section: Turbulence Gridmentioning
confidence: 99%
“…In fact, Laser Doppler anemometry measurements by Goldstein et al [3] at the exit of a can-type combustor resulted in turbulence levels in the order of 15-20%. Additionally, Van Fossen and Bunker [4,5] also surveyed the outlet flow of a similar combustor measuring very high levels of turbulence intensity (up to 30%) and integral length scales (~3 cm). These elevated levels of combustor generated freestream turbulence are extremely challenging for research turbine inlet guide vane testing facilities.…”
Section: Introductionmentioning
confidence: 99%